La religión, una vía para conocer la obra de Edmundo O'Gorman - Andrés Lira (Nuevo mundo - Mundos Nuevos, 2012)
From his early works, Edmundo O'Gorman studied religion, a core element in the historic period he focuses on and which goes from the XVIth to the XXth century. This is the starting point if one wants to plunge into / understand the life and work of the historical characters he studied such as Thomas More (1937) ending up with Edmundo O'Gorman himself with his work Destierro de sombras (1986).